AMPK-ERK/CARM1 Signaling Pathways Affect Autophagy of Hepatic Cells in Samples of Liver Cancer Patients - Qin, Qiu-Fang; Li, Xiao-Jun; Li, Yu-Sang; Zhang, Wei Kevin; Tian, Gui-Hua; Shang, Hong-Cai; Tang, He-Bin (Frontiers in Oncology, 2019)
Liver cancer is one of the most common malignant tumors, with the death rate ranking fourth among all types of cancer. Over the past few decades, several studies have reported that liver tumorigenesis is associated with dysfunction in autophagy. However, the detailed mechanism remains unclear. In this paper, we used tissue micro-array of liver cancer to detect proteins associated with the regulation of autophagic signaling in noncancerous and cancerous regions by immunohistochemical staining. Those proteins contained 4-HNE, p-AMPK, Erk1/2, p-Erk1/2, CARM1, TFEB, LAMP1, and p62. According to the degrees of tumor differentiation in patients (well differentiated group vs moderately and poorly differentiated group), we analyzed each protein’s expression in the ratio of the “cancerous region/noncancerous region” in two groups. Current data showed that there were AMPK-ERK/CARM1 autophagic signaling pathways during the formation of liver cancer. The above-mentioned changes in signals indicated an upregulation of autophagy in cancerous regions, which means overactivated autophagy plays an important role in liver cancer.